IMPLEMENTASI TEKNOLOGI INTERNET OF THING MENUJU SMART LIBRARY - Ginanjar, Sulistya Nur; Istiarni, Atin (LIBRARIA : Jurnal Ilmu Perpustakaan dan Informasi, 2020)
Until now, the internet is still the prima donna for the public to find and get information. The internet is able to provide information to the public in real time, up-to-date, and fast. Therefore, the library is currently faced with the development of science and information that supports the needs of every user in the latest. Collections that are up to date are really needed by users. . In this case, combining library collection information with existing information sources on the internet. Librarians are required to become Smart Librarians in innovating by combining the two information into one container so that it is more efficient in serving users. Innovation by using smart technology in the form of services is expected to be a solution to these problems. Through this smart technology, libraries can get the title of Smart Libraries because they are able to meet the needs of users more quickly, easily, and accurately. This concept is similar to theconcept Smart City. Relying on application technology that can be applied to gadgets user, so that users get the title Smart User because they can easily access information independently. For librarians, this technology becomes a medium for creating ideas that can later be applied to the needs of users. By relying on smart technologies such as Virtual and Augmented Reality, NFC / RFID, Internet of Things, and other supporting technologies, it is hoped thatcan be made Modern Smart Libraries . Of course, the concept of Smart Libraries must be supported by amindset Smart Librarian and Smart User. This paper describes in simple terms the development of libraries by implementing thetechnology Internet of Thing so that it can be used as an illustration for the development ofbased libraries Internet Of Think- in Indonesia.